Accuracy of Gastrointestinal Ultrasound and Calprotectin in the Assessment of Inflammation and its Location in Patients with an Ileoanal Pouch. (24th July 2021) - Ardalan, Zaid S; Friedman, Antony B; Con, Danny; Chandran, Sujievvan; Gibson, David; Pham, Alan; De Cruz, Peter; Tay, Kwang; Bell, Stephen; Rosella, Ourania; Sparrow, Miles P; Gibson, Peter R
Abstract: Background and Aims: In symptomatic patients with ileoanal pouches, pouchoscopy is needed for accurate diagnosis but is invasive. We aimed to assess the utility of non-invasive gastrointestinal ultrasound and faecal calprotectin in ileoanal pouch patients. Methods: Patients with an ileoanal pouch were consecutively enrolled in this cross-sectional study from clinics in Victoria, Australia. The pouchitis disease activity index was used as a reference standard. Video-recorded pouchoscopies were reviewed by three gastroenterologists. Pouch, pre-pouch, and cuff biopsies were reviewed by a single pathologist. Ultrasound was performed by a single gastroenterologist transabdominally and transperineally. Faecal calprotectin was measured from morning stool samples. All examiners were blinded to patients' clinical history. Results: A total of 44 participants had a pouchoscopy, of whom 43 had a faecal calprotectin test and 42 had an ultrasound; 17 had pouchitis, 15 had pre-pouch ileitis, and 16 had cuffitis. Pouch wall thickness of <3 mm was 88% sensitive in excluding pouchitis, and pouch wall thickness of ≥4 mm was 87% specific in diagnosing pouchitis. Transabdominal ultrasound had good utility [area under the curve: 0.78] in diagnosing moderate-severe pre-pouch ileitis. Transperineal ultrasound had good utility for the diagnosis of pouchitis [area under the curve: 0.79]. Faecal calprotectin differentiated inflammatory from non-inflammatory pouch disorders, such as irritable pouch syndrome, with an area under the curve of 0.90. Faecal calprotectin <100 µg/g ruled out inflammatory pouch disorders with a sensitivity of 94%. Conclusions: Faecal calprotectin and ultrasound are accurate and complementary tests to diagnose and localise inflammation of the ileoanal pouch. Prospective studies are needed to validate proposed sonographic indices and calprotectin levels. Graphical Abstract: